Strategi Industrialisasi Hubungan dengan Sektor Lain pada Pembangunan - Eksel Perdian Anggara; Muhammad Yasin (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study attempts to understand how industrial development strategies are closely related to other economic sectors. Like building a house, industrialization is an important foundation country or region's economy, from relying on agriculture to focusing more on industry. Like an ecosystem, each sector needs and influences each other. Emphasizing the importance of cooperation between sectors, such as farmers who provide raw materials for the food industry, or technology companies that create innovations to increase industrial efficiency. In addition, economic diversification, namely developing various types of industries, is also important so that the economy does not rely too much on one sector. Through comparisons between countries, this study good economic Like an orchestra, each sector must play harmoniously to create a beautiful economic melody.